2023
DOI: 10.1136/bmjment-2023-300814
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of transitioning to adult mental health services and associated costs: a cross-country comparison

Rebecca Appleton,
Alastair Canaway,
Helena Tuomainen
et al.

Abstract: BackgroundYoung people are at risk of falling through the care gap after leaving child and adolescent mental health services (CAMHS) despite an ongoing need for mental health support. Currently, little is known about the predictors of transitioning to adult mental health services (AMHS), and associated healthcare and societal costs as young people cross the transition boundary.ObjectiveTo conduct a secondary data analysis exploring predictors of transitioning or falling through the gap and associated costs.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Low referral acceptance and lack of communication between CAHMS and AMHS contribute to the loss of care for approximately half of patients. Such mechanisms result from scarce services and resources, as previously highlighted elsewhere (Eke et al ., 2020; Appleton et al ., 2023; Roberti et al ., 2023b).…”
Section: Discussionmentioning
confidence: 99%
“…Low referral acceptance and lack of communication between CAHMS and AMHS contribute to the loss of care for approximately half of patients. Such mechanisms result from scarce services and resources, as previously highlighted elsewhere (Eke et al ., 2020; Appleton et al ., 2023; Roberti et al ., 2023b).…”
Section: Discussionmentioning
confidence: 99%
“…Some clinical groups are more likely than others to fall through the gap between services (McNicholas et al, 2015). Comparing characteristics between those who transitioned and those who fell through the gap, it was found that only the most severely ill transitioned to AMHS (Appleton et al, 2023), which is in line with findings from other studies (Singh et al, 2008;McNicholas et al, 2015;Gerritsen et al, 2022). Findings from a qualitative interview study showed that young people fell through the gap because of a variety of systemic factors, such as a lack of joined-up care between services, not meeting the illness EDITORIAL © 2024 MA Healthcare Ltd threshold to be eligible for care at AMHS, and a lack of alternative available forms of support (Appleton et al, 2021).…”
Section: The Problem Of Transitionmentioning
confidence: 99%